The effect of tert-butyl hydroperoxide-induced oxidative stress on lean and steatotic rat hepatocytes in vitro - Kučera, Otto; Endlicher, René; Roušar, Tomáš; Lotková, Halka; Garnol, Tomáš; Drahota, Zdeněk; Cervinková, Zuzana (Oxidative medicine and cellular longevity, 2014)
Oxidative stress and mitochondrial dysfunction play an important role in the pathogenesis of nonalcoholic fatty liver disease and toxic liver injury. The present study was designed to evaluate the effect of exogenous inducer of oxidative stress (tert-butyl hydroperoxide, tBHP) on nonfatty and steatotic hepatocytes isolated from the liver of rats fed by standard and high-fat diet, respectively. In control steatotic hepatocytes, we found higher generation of ROS, increased lipoperoxidation, an altered redox state of glutathione, and decreased ADP-stimulated respiration using NADH-linked substrates, as compared to intact lean hepatocytes. Fatty hepatocytes exposed to tBHP exert more severe damage, lower reduced glutathione to total glutathione ratio, and higher formation of ROS and production of malondialdehyde and are more susceptible to tBHP-induced decrease in mitochondrial membrane potential. Respiratory control ratio of complex I was significantly reduced by tBHP in both lean and steatotic hepatocytes, but reduction in NADH-dependent state 3 respiration was more severe in fatty cells. In summary, our results collectively indicate that steatotic rat hepatocytes occur under conditions of enhanced oxidative stress and are more sensitive to the exogenous source of oxidative injury. This confirms the hypothesis of steatosis being the first hit sensitizing hepatocytes to further damage.
Keywords: Non-alcoholic Fatty Liver Disease; reaktivní formy kyslíku; Cells, Cultured; Glutathione; peroxidace lipidů; L-laktátdehydrogenasa; Oxidative Stress; hepatocyty; krysa rodu Rattus; terc-butylhydroperoxid; membránový potenciál mitochondrií; tert-Butylhydroperoxide; kultivované buňky; dieta s vysokým obsahem tuků; Hepatocytes; potkani Wistar; Rats, Wistar; nealkoholová steatóza jater; mužské pohlaví; zvířata; glutathion; Membrane Potential, Mitochondrial; L-Lactate Dehydrogenase; oxidační stres; Rats; Animals; Reactive Oxygen Species; Male; Malondialdehyde; Lipid Peroxidation; malondialdehyd; Diet, High-Fat